FDI and CO2 emissions in developing countries: the role of human capital - Khan, Muhammad; Rana, Arslan Tariq; Ghardallou, Wafa (Natural hazards (Dordrecht), 2023)
FDI inflows remain an important source of economic growth and technology transfer for developing countries. However, the proponents of the pollution haven hypothesis (PHH) argue that FDI inflows may result in the production of polluted goods in poor economies. The empirical testing of PHH reveals conflicting outcomes on the subject. This study argues that foreign firms’ choice of specific technologies and hence the validity of PHH can be determined by host countries’ level of education. For developing economies having low levels of schooling, FDI inflows will accompany polluted technologies. Nonetheless, when education levels exceed certain thresholds, FDI inflows may reduce CO 2 emissions. For our empirical investigation, we rely upon a large panel of 108 developing countries during 2000–2016. Our estimated outcomes, based on the panel cointegration method and panel vector error correction methods (P-VECM), confirm these moderating effects of human capital in the FDI–CO 2 emissions nexus. The empirical results also confirm the presence of the environmental Kuznets curve (EKC) for developing countries. These results have important policy implications for the sample economies.